Accelerating development of engineered T cell therapies in the EU: current regulatory framework for studying multiple product versions and T2EVOLVE recommendations - Ammar, Delphine; Schapitz, Inga; Luu, Maik; Hudecek, Michael; Meyer, Miriam; Taps, Timmothy; Schröder, Bernd; Ivics, Zoltán; Sanges, Carmen; Franz, Paul; Koehl, Ulrike; Negre, Helene; et al. (Frontiers in Immunology, 2023)
To accelerate the development of Advanced Therapy Medicinal Products (ATMPs) for patients suffering from life-threatening cancer with limited therapeutic options, regulatory approaches need to be constantly reviewed, evaluated and adjusted, as necessary. This includes utilizing science and risk-based approaches to mitigate and balance potential risks associated with early clinical research and a more flexible manufacturing paradigm. In this paper, T2EVOLVE an Innovative Medicine Initiative (IMI) consortium explores opportunities to expedite the development of CAR and TCR engineered T cell therapies in the EU by leveraging tools within the existing EU regulatory framework to facilitate an iterative and adaptive learning approach across different product versions with similar design elements or based on the same platform technology. As understanding of the linkage between product quality attributes, manufacturing processes, clinical efficacy and safety evolves through development and post licensure, opportunities are emerging to streamline regulatory submissions, optimize clinical studies and extrapolate data across product versions reducing the need to perform duplicative studies. It is worth noting that this paper is focusing on CAR- and TCR-engineered T cell therapies but the concepts may be applied more broadly to engineered cell therapy products (e.g., CAR NK cell therapy products).